Volatility comovements in international stock markets: effects of the global financial crisis - Gabriel, Vítor Manuel de Sousa; Saraiva, Helena Isabel Barroso (Millenium - Journal of Education, Technologies, and Health, 2016)
This study examines the effects of the global financial crisis on the volatility of emerging stock markets. With this goal, twenty emerging stock markets have been analysed, in the period between May 2002 and December 2013. In order to estimate market volatility, the EGARCH model was implemented. In order to analyse volatility behaviour and the influence of the global financial crisis, both in the short and long-term, the extreme values test and the principal component analysis were applied. Conclusions revealed that the stock market volatility showed similar behaviours for the two time horizons, and the global financial crisis represented a key role in strengthening and deepening these similar behaviours, limiting a possible diversification strategy.